2019
DOI: 10.1097/gco.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Tranexamic acid in benign gynecology

Abstract: Purpose of review Bleeding at the time of benign gynecologic surgery, as well as from benign gynecologic conditions, is a major source of morbidity for many women. Few nonhormonal medical options exist for the treatment of heavy menstrual bleeding, and to reduce surgical bleeding during major gynecologic surgery. Interest in Tranexamic acid (TXA) as a means to reduce surgical blood loss has been growing across many surgical specialties. This review focuses on applications for TXA as a means to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…TXA, as an antifibrinolytic agent blocking the lysine binding site of plasminogen, can effectively reduce the duration and quantity of blood loss and has been used in orthopaedic surgery [39][40][41]. Various routes of TXA administration have been used in surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…TXA, as an antifibrinolytic agent blocking the lysine binding site of plasminogen, can effectively reduce the duration and quantity of blood loss and has been used in orthopaedic surgery [39][40][41]. Various routes of TXA administration have been used in surgical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Offlabel uses of oral, topical, and intravenous TXA includes brutally bleeding patients requiring massive transfusion protocols or when hyper-fibrinolysis is demonstrated and combat trauma patients requiring at least one unit of blood within 24 hours of presentation. Another off-label intravenous use of TXA is in surgical operations to reduce blood loss [10].…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…It is shown that TXA administration intravenously can reduce maternal mortality from post-partum hemorrhage without increasing the risk for thromboembolic events [ 12 ]. It is also used within elective orthopedic, gynecology and urologic surgery, decreasing perioperative bleeding and the need for transfusions [ 13 - 15 ]. In the CRASH-2 study, a big multicenter study involving 20,211 adult trauma patients with or at risk for significant bleeding, also showed TXA’s effectiveness in reducing mortality, if given early in the process, like other studies have shown [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%